The role of the fibrinolytic system in female reproductive disorders and depression - Silvia Hoirisch-Clapauch; Benjamin Brenner (Thrombosis Update, 2020)
Tissue plasminogen activator (tPA) and urinary plasminogen activator (uPA or urokinase) have important functions in the extracellular matrix. In the reproductive system, for example, tPA and uPA mediate tissue remodeling required for ovulation, endometrial receptivity for embryo implantation, placental angiogenesis, and uterine vascular adaptation to pregnancy. In the brain, the two proteases influence a variety of processes that contribute to resilience, and depression remission.Postprandial hyperinsulinemia – not to be confounded with insulin resistance – inhibits physiological remodeling of female reproductive organs and the brain, because insulin stimulates the production of plasminogen activator inhibitor-1 (PAI-1), a major regulator of plasminogen activators. Conditions accompanied with postprandial hyperinsulinemia in non-diabetic individuals include a sedentary lifestyle combined with a high-carbohydrate, low-protein diet; binge eating disorder, defined as an uncontrolled consumption of large amounts of high-carbohydrate food, in the absence of compensatory behaviors such as vomiting or exercising; and overexercising, such as in elite athletes, who maintain their weight with a high-carbohydrate diet.Here, we explore how lifestyle-related hyperinsulinemia, by impairing extracellular proteolysis, contributes to the pathogenesis of polycystic ovary syndrome, implantation failure, early miscarriage, preeclampsia, and atypical depression. We also analyze the relationships between these disorders, and their association with venous thromboembolism and ischemic heart disease. As defective matrix remodeling is likely amenable to lifestyle interventions that maintain postprandial insulin levels within normal range, we review the evidence supporting this.